Real world applications and analysis of V2X communication in the 2016 Grand V2X communication in the 2016 Grand Cooperative Driving Challenge - Nguyen, Björnborg (My University, 2016)
This master thesis analyses the performance of one particular existing open software solution for vehicular communication for intelligent transport systems which is the GeoNetworking library and Vehicle adapter which abide the European Telecommunications Standards Institute’s directives and regulations regarding vehicular communication under the name of ITS-G5. In terms of performance, latency and the throughput capabilities of the software were observed and studied in both controlled environment and real world case scenario. This study greatly benefited from the i-game’s project: 2016 grand cooperative driving challenge, where several automated vehicle systems equipped with vehicle communication systems were participating in three distinct scenarios demonstrating the different applications of cooperation using vehicular communication; these scenarios are emergency vehicle-, intersection-, and merging scenario. Data was gathered through benchmarking software tools in a simulated environment and interviews with the participating teams. The results of the Vehicle adapter on the GeoNetworking library and proposed hardware solution shows that the latency was less than 0.005 s when neglecting the data transfer time between the layers of the system while throughput benchmarked at 98.41 messages per second at ideal settings. On the other hand, the findings of the benchmarked throughput may be improved since it contradicts the observed performances of participating vehicle systems in the i-game’s driving challenge. Still, the proof of concept of vehicle communications was clearly demonstrated on a small scale with nearly no signs of performance problems during the competition. From interviews, some teams in the competition expressed their concerns regarding the vehicle communication in various aspects. One of the pressing issues is the information theory and game theory; fundamentally down the question: can your system trust other’s broadcast information for collaboration purposes? They were also concerned for the user integrity and network security which are strongly associated with network communication regardless of the applications. However, vehicle communications show significant promises and contributions to new types of application in cooperative behaviors in both automated- and autonomous vehicles. The most obvious application would be platooning which would greatly benefit from the shared information as well handshaking protocols for complex scenarios as platoon merging. Further on a macroscopic level, it could counteract the traffic congestion as well reduce the fuel consumption of the vehicles.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport